Dama dentition: a new tooth eruption and wear method for assessing the age of fallow deer (Dama dama) - Bowen, Frazer; Carden, R.F.; Daujat, J.; Grouard, Sandrine; Miller, Holly; Perdikaris, Sophia; Sykes, Naomi (Wiley, 2016)
Reliable ageing techniques for wild animals are notoriously challenging to develop because of the scarcity of sizeable collections of known‐age specimens. Without such techniques it is difficult to reconstruct hunting patterns, which is a significant problem for the examination of assemblages from pre‐farming cultures. This paper presents a new method, based on mandibular tooth eruption and wear, for assessing the age of fallow deer. The method was developed from a large collection (n = 156) of known‐age Dama dama specimens, has been blind tested by members of the zooarchaeological community and represents a user‐friendly system with the potential to generate large compatible datasets through which the dynamics of human–Dama relationships can be examined.